I nuovi orizzonti delle decisioni di fine vita e della donazione di organi in Italia (BioLaw Journal - Rivista di BioDiritto, 2023)
The aim of this paper is to offer some considerations on a new field of investigation in biolaw, which has emerged from the combination of two classic and traditionally separate topics: end-of-life decisions and organ donation. The idea of exploring the opportunities arising from these separate issues has begun to gain ground in our legal system, as clearly demonstrated by the intervention of the Italian Committee for Bioethics on controlled donation after circulatory determination of death. Indeed, the evolution of the debate on the end-of-life in Italy (Constitutional Court, judgement No 242 of 2019) raises some questions on a closely related topic, that of organ donation following euthanasia or physician-assisted suicide, especially in light of the experiences of other countries where this procedure is already practiced and widespread.
Keywords: Organ donation; end-of-life decisions; controlled donation after circulatory determination of death; medical assistance in dying; organ donation after euthanasia